Analysis of Borax in Ground Red Chilies in the Traditional Markets of Jambi City - Havizur Rahman; Mia Prajuwita; Dika Zamri Yanni; Putri Maya Sari; Intan Lestari (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
Preservatives are one of the food additives used to preserve perishable foods. Based on Peraturan Menteri Kesehatan RI No. 033 Tahun 2012 about food additives, sodium tetraborate or borax is classified in additives, which are prohibited being used in food. However in reality, there are still used. The purpose of this study is to identify and measure levels of borax compounds in ground red chilies that are sold in the traditional markets of Jambi city. Qualitative analysis of borax in ground red chilies using a color test method using Tumeric paper. While the quantitative analysis of borax in ground red chilies using UV-Vis Spectrophotometry at the wavelength of 550 nm. Borax identification results showed that 25 samples the ground red chilies tested contained borax with average concentration 1,998 mg/gram of borax compound. Analysis of the results of the test of borax content with SPSS using the Chi-square test indicated that there was no relationship between the selection of ground red chilies with the use of borax as a food preservative.